Effectiveness and Safety of Abatacept in Moderate to Severe Rheumatoid Arthritis - Lucía Cortejoso-Fernández; Rosa María Romero-Jiménez; María Sagrario Pernía-López; María Montoro-Álvarez; María Sanjurjo-Sáez (Frontiers Media S.A., 2011)
Purpose: Abatacept was approved in our hospital by the Pharmacy and Therapeutics Committee for treatment of moderate to severe rheumatoid arthritis (RA) in adult patients with inadequate response or intolerance to disease modifying antirheumatic drugs (DMARDs), including at least one anti-tumour necrosis factor (anti-TNF). The objectives of this study were to analyze compliance with our protocol and to evaluate effectiveness and safety of abatacept in our patients. Methods: We performed a descriptive longitudinal study of patients with RA treated with abatacept between August 2008 and May 2010 in our day care unit. We reviewed clinical records and recorded the following data: sex, age, weight, year of diagnosis, previous antirheumatic treatments and reasons for withdrawal of anti-TNFs, indication for abatacept, dose and date of administration, Disease Activity Score (DAS28) and adverse events. Effectiveness was evaluated using the European League Against Rheumatism (EULAR) criteria. Results: We recruited 16 patients. Mean follow-up time was 10.4 (SD: 6.1) months. All patients had been previously treated with DMARDs, including at least one anti-TNF, and the mean dose of abatacept was 9.4 (SD: 1.4) mg/kg. During the first 6 months of treatment, 11/16 of patients experienced a decrease in their DAS28 value, but only 5/16 achieved a satisfactory response. Dyspnea was the most frequent adverse event (7/16), followed by fatigue and asthenia (6/16) and dry skin (5/16). Conclusions: The indication for abatacept in our hospital complied with the protocol approved by the Pharmacy and Therapeutics Committee. Only 5/16 of patients achieved a satisfactory response; however, it should be noted that these patients had moderate to severe RA that was refractory to other treatments. Adverse reactions were consistent with those described in the summary of product characteristics. Further studies with larger cohorts are needed to analyze the long-term safety and effectiveness profile in clinical practice. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.